Improvement in growth and yield of Indian mustard by using micro and secondary nutrients fortified FYM in calcareous soil (Journal of Oilseed Brassica, 2026)
A field experiment was conducted to enhance the micro and secondary nutrient availability to Indian mustard (Brassica juncea L) in arid and semi-arid regions using split plot design with three replications. The experiment was consisted with three treatments of FYM level (control, 5 t ha-1 and 10 t ha-1) and five treatment of nutrient sources (control, 2.5 kg Zn + 1 kg B+ 5 Kg Fe + 10 kg S ha-1, 5 kg Zn + 2 kg B+ 10kg Fe +20 S kg ha-1, 2.5 kg Zn + 1 kg B+ 5 Kg Fe +10 kg S enriched with FYM @ 500 kg ha-1 and 5 kg Zn + 2 kg B+ 10kg Fe+20 kg S enriched FYM @ 500 kg ha-1). The results revealed that application of FYM @ 10 t ha-1 along with5 kg Zn + 2 kg B + 10 kg Fe + 20 kg S enriched FYM @ 500 kg ha-1 found significantly (p=0.05) improved plant height, number of primary and secondary branches, chlorophyll content (90 DAS), LAI, basal girth, maximum seed yield (29.64 q ha-1), stover yield (76.25q ha-1) and oil content (12.78q ha-1). Such studies could play crucial role in balance application of plant nutrient for enhancing Indian mustard yield.